Effect of Acetaminophen Against the Background of Alimentary Protein Deficiency on the Features of Sulfur-Containing Amino Acids Metabolism in Rats - Nykolaichuk, Ivanna; Kopylchuk, Нalyna (My University, 2022)
In recent years, there has been extensive evidence of the involvement of disorders in the metabolism of sulfur-containing amino acids - methionine, cysteine and homocysteine - in the development of several diseases. These amino acids share common degradation pathways, and their intermediates play a role in regulating the activity of homocysteine remethylation and enzymes transsulfuration. In this study, we aimed to evaluate the effect of acetaminophen on the background of dietary protein deficiency on the metabolism of sulfur-containing amino acids in rats: distribution of sulfur-containing amino acids - homocysteine, cysteine and methionine − in blood serum and hepatocytes, activity of key enzymes of the transsulfuration pathway of homocysteine metabolism - сystathionine beta-synthase, сystathionine gamma-lyase. During the experiment, the experimental animals consumed a semi-synthetic diet AIN-93 in accordance with the recommendations of the American Institute of Nutrition. In order to model the alimentary protein deprivation rats received a low-protein diet daily for 28 days, which contained 1/3 of the generally accepted daily requirement of protein. After four weeks of keeping animals on an experimental diet, acute toxic damage with acetaminophen was modelled. The toxin was administered at 1250 mg/kg of animal weight as a suspension in a 2% solution of starch gel once a day for 2 days. Our results indicate that the conditions of alimentary protein deprivation and acetaminophen toxic injury in hepatocytes and blood serum of animals disrupts the distribution of sulfur-containing amino acids (decrease in methionine, increase in cysteine concentration) with the development of hyperhomocysteinemia: in the absence of dietary protein - a mild form, with the introduction of toxic doses of acetaminophen - moderate. The results confirm the causal relationship between the functioning of the transsulfuration pathway of homocysteine (decreased cystathionine β-synthase activity with simultaneous activation of cystathionine γ-lyase in animal hepatocytes) and the maximum increase in the level of this amino acid in blood serum under conditions of acetaminophen-toxic injury. Elevated blood homocysteine levels can therefore be considered as a prognostic marker of functional abnormalities in the liver transsulfuration pathway and can be used in the diagnosis of hepatic pathologies.
Keywords: Amino Acids; Sulfur; Methionine; Cysteine; Homocysteine; Metabolism; Transsulfuration; Сystathionine Beta-Synthase; Сystathionine Gamma-Lyase; Acetaminophen; Alimentary Protein Deficiency; Liver; Rats